2022
DOI: 10.1002/adma.202201248
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Conductance in Memristive Devices: Fundamentals, Developments, and Applications

Abstract: Quantum effects in novel functional materials and new device concepts represent a potential breakthrough for the development of new information processing technologies based on quantum phenomena. Among the emerging technologies, memristive elements that exhibit resistive switching, which relies on the electrochemical formation/rupture of conductive nanofilaments, exhibit quantum conductance effects at room temperature. Despite the underlying resistive switching mechanism having been exploited for the realizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 244 publications
(420 reference statements)
4
54
0
3
Order By: Relevance
“…Interestingly, the distribution of the device conductance over cycling in the LRS normalized with respect to the fundamental quantum of conductance G 0 reported in Figure d shows that the device internal state of conductance is lower than G 0 ( G / G 0 mean value of 0.22, standard deviation of 0.03). While values close to G 0 are expected when the filament size reaches the atomic scale favoring the formation of a quantum point contact, values of G < G 0 mean that the formed filament does not allow the complete transmission of the electron wave packet. This corresponds to the tunneling regime through a subband.…”
Section: Resultsmentioning
confidence: 96%
“…Interestingly, the distribution of the device conductance over cycling in the LRS normalized with respect to the fundamental quantum of conductance G 0 reported in Figure d shows that the device internal state of conductance is lower than G 0 ( G / G 0 mean value of 0.22, standard deviation of 0.03). While values close to G 0 are expected when the filament size reaches the atomic scale favoring the formation of a quantum point contact, values of G < G 0 mean that the formed filament does not allow the complete transmission of the electron wave packet. This corresponds to the tunneling regime through a subband.…”
Section: Resultsmentioning
confidence: 96%
“…Pulse measurements were performed in Fig. 5 c and d to describe the quantized conductance [ 62 64 ]. Conductance calculated with the voltage of 0.5 V was induced by adding write pulses at 0.5 s intervals.…”
Section: Resultsmentioning
confidence: 99%
“…6 Moreover, the devices showing quantized conductance have also been explored for various applications such as selectors, logic circuits, synaptic weight elements, leaky integrated-and-fire neurons, and so on. 7 For polymerbased devices, Gao et al have observed quantized conductance in a Ag/poly(3-hexylthiophene) [6,6]:-phenyl-C61-butyric acid methyl ester/ITO device under voltage sweep and pulse measurements. 8 Quantized conductance states of integer multiples of single atomic point contact and partially quantized states have been reported using graphene submicron-sized nanoplatelets embedded in a 3-hexylthiophene layer.…”
Section: Introductionmentioning
confidence: 99%